Ameliorating Effects of Arsenic-Induced Toxicity On The Histology Of Vagina And Reproductive Hormones Of Female Sprague Dawley Rats - Mir, Amaidah; Mir, Urfa Zaryab; Yasmeen, Maria; Ahmad, Mushtaq; Huma, Kanwal; Khurshid, Iram Kehkashan (Journal of Rawalpindi Medical College, 2024)
Objective: To find out the toxic effects of arsenic on the histology of the vagina and reproductive hormones of female Sprague Dawley rats. Methods: 60 female Sprague Dawley rats were divided into control group A and experimental group B with 30 rats in each group. The gross weight of all the rats was checked before and at the end of the experiment. After one week of acclimatization, the control group was administered 10ml of distilled water by oral gavage daily for 14 days and the experimental group was administered 4µg of sodium arsenite dissolved in 10ml of distilled water by oral gavage daily for 14 days. After being euthanized by chloroform inhalation on day 15, blood from each rat was drawn by a single intra-cardiac puncture and stored for biochemical analysis. After that, rats were sacrificed and the whole reproductive tract was removed and vaginal sections were prepared and stained with hematoxylin and eosin (H&E ). The histological parameters were analyzed by using Image J software. Whereas, biochemical parameters e.g. serum LH and FSH levels were analyzed by ELISA. Results: After exposure to a low dose of arsenic administered for a short period, the gross weight of rats, weight of reproductive tract, height of vaginal epithelium and serum FSH and LH values were significantly reduced in experimental animals as compared to control animals with p-value < 0.05. Conclusion: Low dose of arsenic given via contaminated drinking water for a short period is very toxic to the female reproductive tract which is evident by the histological changes in the vagina and deranged hormonal profile of female Sprague Dawley rats. Keywords: Arsenic, FSH, Free radicals, LH, Oxidative stress, Vagina.